Rola informacji na rynku produktów banków hipotecznych - Natalli, Krzysztof; Szczepanik, Maciej (The Role of Information at the Market of Mortgage Banks' Products, 2005)
The purpose of this article is to present the role of information and to show the influence of an economic subjects’ informational activity on the market of mortgage credits given by Polish mortgage banks. The article is divided into 4 parts. In the first and the second part of the article basic definitions of the information theory and the classification of the uncertainty of economic activity are described. The simple example presents how a bank can reduce the uncertainty of the partner’s behaviour. Costs and benefits of an informational activity are described in the third part of the paper. At the end of the article a special attention is paid to the analysis of the clarity of Polish mortgage credits market.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1089, s. 42-58